Experience and individual motivation affect the sexual performance of male goats at different times of the year - Ayala-Pereyro, Karen; Terrazas, Angelica; González-Díaz, Francisco R.; Ibarra-Trujillo, Rocío; Cano-Suárez, Paolo; Soto, Rosalba (Frontiers in Ethology, 2025)
IntroductionAlthough there is extensive research on sexual behavior in goats, little is known about the effects caused by individual variations in males.ObjectiveThe present study aimed to evaluate, on an individual basis, the sexual behavior in developing male bucks, during their first year of life, throughout three times across the year.MethodsFrequencies and latencies of copulation, recovery period, sniffing, approximation, licking, pawing, flehmen, self-marking, female seeking, and fake mounting were assessed in six bucks. With the sum of the standardized frequencies of each behavior, a sexual index was constructed, where negative values indicate low sexual performance, contrary to high values. At the beginning of the study, males were 10 months old, and when the study was over, they were 17 months old. The study was conducted in three stages: stage 1 (March 3rd to March 25th), stage 2 (April 8th to April 20th), and stage 3 (September 21st to October 12th). Each male was tested in the presence of two receptive females, seven times every third day in each stage, for 10 min each test.ResultsWhen comparing between males, it was found that male 6 had a longer latency of copulation at stage 2 (P ≤ 0.01) and showed a similar trend toward longer latency at stage 3 (P < 0.09). When comparing within the same male over time, the latency of copulation in male 5 changed across each stage (P = 0.03). At the same time, male 6 showed a tendency to decrease the latency of copulation as the study progressed (P = 0.06). Regarding the sexual index, male 3 had the highest sexual index in stage 3 (P ≤ 0.02); in contrast, males 5 and 6 had the lowest at almost all stages. Finally, males 1, 2, 3, and 4 improved their sexual index as the study advanced (P ≤ 0.01); in contrast, males 5 and 6 did not (P ≥ 0.05).ConclusionsIn bucks, the sexual performance improved with experience, but only in those with high motivation.